2023
DOI: 10.1002/ncp.10990
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solid food provision within 24 hours of hospital admission on clinical outcomes for adult patients with acute pancreatitis: A literature review

Abstract: Acute pancreatitis (AP) is a common gastrointestinal disease necessitating hospitalization, with incidence increasing both in the United States and worldwide. Some recent guidelines for hospitalized patients with AP recommend initiation of oral feeding within 24 h of admission; however, a lack of clarity regarding feeding time and diet orders in clinical practice still exists. This review presents recent randomized clinical trials regarding feeding administration for patients with mild to moderate AP. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…In addition to the prompt treatment of severe cases, a more accurate classification of pancreatitis can help to better treat patients with mild to moderate cases. Randomized clinical trials on patients with mild to moderate AP have shown that starting a low-fat solid oral diet within 24 h of admission to the hospital does not increase instances of negative outcomes and may also provide positive benefits for patients with AP [44]. Therefore, it may be beneficial to monitor the status of patients with pancreatitis more frequently to resume this diet promptly when symptoms subside.…”
Section: Point-of-care Testingmentioning
confidence: 99%
“…In addition to the prompt treatment of severe cases, a more accurate classification of pancreatitis can help to better treat patients with mild to moderate cases. Randomized clinical trials on patients with mild to moderate AP have shown that starting a low-fat solid oral diet within 24 h of admission to the hospital does not increase instances of negative outcomes and may also provide positive benefits for patients with AP [44]. Therefore, it may be beneficial to monitor the status of patients with pancreatitis more frequently to resume this diet promptly when symptoms subside.…”
Section: Point-of-care Testingmentioning
confidence: 99%